Technological and Management Issues of Implementing Big Data Models in Smart Cities - Tadeusz A. GRZESZCZYK; Maciej MASIAK (Communications of International Proceedings, 2022)
Implementation issues of smart cities are primarily seen in the literature as a framework that should be improved mainly in terms of increasingly perfect information and communication technologies (ICT), which should keep up with the challenges related to urbanization progress. The motive behind this study is to point out that currently implemented projects concerning big data models in smart cities require looking for appropriate approaches in IT technologies and managerial solutions. Managers of such projects should therefore develop digital competencies and soft skills necessary for human resource management. The paper presents the selected technological and management issues related to implementing big data models in smart cities adequate for modern investment technology projects. The research used literature studies, participant observation, and comparative analyzes of documents and selected big data technologies. Based on observations and comparative analyzes, barriers to implementing big data technologies in the smart city were identified. Particular attention was paid to complex management aspects related to building cooperation in projects between diverse scientific, business and public administration environments. The results of these studies will allow for the continuation of research associated with the indication of suggested directions for the improvement of management systems adequately to the challenges related to applying various projects that are planned and implemented in smart cities.
Keywords: Smart City; Big Data Models; Technological And Management Issues.